Posisi Semi Prone Dapat Memberikan Kenyamanan pada Anak dengan Pneumonia - Nurbetti Br Ginting; Nani Nurhaeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of the semi-prone position on comfort in children with pneumonia. The method used is an integrated literature review. The journals reviewed range from 2017 to 2020 using the ScienceDirect, BMC, PubMed, Research Gate, Taylor & Francis databases. Still, only three journals were included as inclusion criteria. The results of the study showed that semi-prone therapy had a relaxing effect on children. This therapy can decrease respiratory rate (p = 0.04) in children short of breath and increase oxygen saturation (p = 0.045) in children who have CPAP installed. In addition, the child is not fussy and still sleeps soundly when given a semi-prone position. In conclusion, semi-prone therapy is an easy therapy and has excellent benefits in children with pneumonia and can be applied in an inpatient room. Keywords: Child Pneumonia, Comfort, Semi Prone Position